An acidic microenvironment sets the humoral pattern recognition molecule PTX3 in a tissue repair mode - Doni, A.; Musso, T.; Morone, D.; Bastone, A.; Zambelli, V.; Sironi, M.; Castagnoli, C.; Cambieri, I.; Stravalaci, M.; Pasqualini, F.; Laface, I.; Valentino, S.; et al. (Rockefeller University Press, 2015)
Pentraxin 3 (PTX3) is a fluid-phase pattern recognition molecule and a key component of the humoral arm of innate immunity. In four different models of tissue damage in mice, PTX3 deficiency was associated with increased fibrin deposition and persistence, and thicker clots, followed by increased collagen deposition, when compared with controls. Ptx3-deficient macrophages showed defective pericellular fibrinolysis in vitro. PTX3-bound fibrinogen/fibrin and plasminogen at acidic pH and increased plasmin-mediated fibrinolysis. The second exon-encoded N-terminal domain of PTX3 recapitulated the activity of the intact molecule. Thus, a prototypic component of humoral innate immunity, PTX3, plays a nonredundant role in the orchestration of tissue repair and remodeling. Tissue acidification resulting from metabolic adaptation during tissue repair sets PTX3 in a tissue remodeling and repair mode, suggesting that matrix and microbial recognition are common, ancestral features of the humoral arm of innate immunity.